In vitro micropropagation of Aloe elegans Tod. using offshoot cuttings - Mebrahtom Welehaweria; Desta Berhe Sbhatu (BMC Research Notes, 2023)
Abstract Objective Aloe elegans Tod. is an ecologically, environmentally, medicinally, and commercially useful aloe species in Ethiopia and Eritrea. Unfortunately, it is highly threatened due to industrial and urban expansion and traditional mining and agricultural activities. As a consequence, it is included in the IUCN List of Threatened Species since 2013. The plant is getting thinly populated in many parts of the Tigrai floristic region since it is being exploited for traditional and commercial purposes. Therefore, this study was aimed to develop a reproducible, large-scale micropropagation protocol using offshoot cuttings in Murashige and Skoog (MS) media enriched with plant growth regulators (PGRs). Results Sterilized explants cultured in full-strength MS media enriched with 0.25 mg/L benzyl amino purine (BAP) and 0.10 mg/L naphthaleneacetic acid (NAA) resulted in 100% healthy and live (i.e., initiated) explants after four weeks of initiation study. Unsupplemented initiation media (control) yielded only 14.3% initiated explants. The initiated explants were tested for their shooting response to produce microshoots by incubating in different concentrations and combinations of BAP and NAA for four weeks. Fewer days to shooting (13.0 ± 1.0 days), higher mean shoot number (5.0 ± 1.0), and higher mean shoot length (9.20 ± 2.35 cm) were observed with 1.0/0.50, 1.0/0.25, and 1.0 /0.50 mg/L BAP/NAA combinations, respectively. The rooting responses of the microshoots toward producing plantlets were also tested by incubating them in half-strength MS media enriched with different concentrations of NAA and indole-3-butyric acid (IBA) for four weeks. Fewer mean days to rooting (12.0 ± 1.0 days), higher mean root number (8.0 ± 4.0), and higher mean root length (7.53 ± 3.03 cm) were observed in MS media enriched with 0.75, 0.75, and 1.25 mg/L IBA, respectively. The responses of A. elegans plantlets to primary (in greenhouse) and secondary (in nursery shade and direct sunlight) acclimatization in coco peat, composted soil, and manured soil media were high – with survival percentages of 87.5–97.8% in three to four weeks.